The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.32604/csse.2023.024375
|View full text |Cite
|
Sign up to set email alerts
|

Optical Ciphering Scheme for Cancellable Speaker Identification System

Abstract: Most current security and authentication systems are based on personal biometrics. The security problem is a major issue in the field of biometric systems. This is due to the use in databases of the original biometrics. Then biometrics will forever be lost if these databases are attacked. Protecting privacy is the most important goal of cancelable biometrics. In order to protect privacy, therefore, cancelable biometrics should be non-invertible in such a way that no information can be inverted from the cancela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Other cancelable biometric systems are presented in [7,8]. The authors of [7] provided a cancelable method for speech recognition based on encryption algorithms.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Other cancelable biometric systems are presented in [7,8]. The authors of [7] provided a cancelable method for speech recognition based on encryption algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…An additional encryption algorithm is implemented using double random phase encoding (DRPE) to increase the security level of the encrypted signals. The proposed methodology was improved in [8] to protect the privacy of biometric data using cancelable biometrics where the data cannot be inverted so that the user information is kept private and secured. The authors suggested a hybrid algorithm based on the Fourier transform and Jigsaw transform.…”
Section: Related Workmentioning
confidence: 99%
“…The design of cancelable biometric transforms makes the recovery of the original biometric data a computationally hard process [8,9]. Several studies have been presented to generate cancelable biometrics [10][11][12][13]. Ratha et al [14] proposed a method for identification based on a cancelable geometric fingerprint framework.…”
Section: Related Workmentioning
confidence: 99%
“…18,19 Addressing this gap, our research introduces a novel optical hashing and compression paradigm, ingeniously leveraging the SWIFFT family of post-quantum hashing algorithms. [20][21][22][23][24][25][26][27][28][29][30] This innovative approach marks a significant leap forward, eschewing the conventionally employed slow, high-resolution CMOS cameras in favor of ultra-fast, signal-triggered CMOS detector arrays. The transition to these advanced detector arrays catalyzes a remarkable acceleration in information acquisition rates.…”
Section: Introductionmentioning
confidence: 99%
“…As computational power continues to scale, particularly with the looming advent of quantum computing, traditional cryptographic methods face potential obsolescence. [62][63][64][65][66][67][68][69] In this context, post-quantum hashing algorithms stand as a bulwark against future threats, ensuring that our data remains secure against even the most advanced computational attacks. 70,71 The implementation of this optical hashing and compression strategy engenders a suite of enhancements across the computational spectrum.…”
Section: Introductionmentioning
confidence: 99%